Drivers and barriers influencing consumers’ online collaborative clothing consumption practices in the South African market - Jacobs, B.M. (Bertha Margaretha) (University of Pretoria, 2023)
Dissertation (MConsumer Science (Clothing Management))--University of Pretoria, 2021.